An interesting case of placenta percreta - Thangella, Likitha; Upadhyaya, Vaishali; Jain, Vaishali (Indian Journal of Case Reports, 2020)
Placenta percreta is a condition where chorionic villi penetrate the entire myometrium, extending beyond uterine serosa. Here, we present an interesting case of placenta percreta in a 32-year-old lady with a previous history of the lower segment cesarean section. Initial ultrasonography had revealed oligohydramnios and an anterior low lying placenta with myometrial invasion, suggestive of placenta increta. Subsequently, a pre-operative magnetic resonance imaging demonstrated further invasion of the uterine serosa and bladder dome involvement which confirmed placenta percreta.